The relationship between aesthetic preferences of people for ceramic tile design and neural responses: An event-related potential study - Chen, Jiayin; Cheng, Yue (Frontiers in Human Neuroscience, 2022)
The aesthetic preferences of people can determine the success of a design and are often closely related to design features. The discovery of designs that match user preferences can provide a reference for designers. Ceramic tiles are widely used in environmental design; however, little attention has been paid to the aesthetic preferences of people for tiles. This study aimed to explore the relationship between aesthetic preferences for tile design and neural responses. In this study, two groups of tiles with different preference levels were randomly presented to 16 participants, and their electroencephalograms were recorded. The mean amplitudes of event-related potentials were analyzed by ANOVA. The results showed that: (1) the aesthetic preferences of people for tiles could modulate brain activity; (2) tiles that people liked triggered higher N100 amplitudes; (3) tiles that people disliked triggered higher P200 and late positive potential (LPP) amplitudes. These results suggest that N100, P200, and LPP are significantly related to the aesthetic preferences of people for ceramic tiles. The difference in N100 and P200 amplitudes indicates that participants developed aesthetic perceptions of the tiles in the early and middle stages of vision and formed different attention allocations to tiles with varying levels of aesthetic preference; in the middle and late stages of visual processing, the difference in the LPP amplitude indicates that the impression of people for tiles is further deepened in the later stage, forming a top-down emotion-driven evaluation. Exploring the relationship between the aesthetic preferences of people and neural responses is significant in establishing objective aesthetic judgment indicators for tiles and understanding the process of aesthetic cognition. This study provides relevant information for quantitative aesthetic assessments of environmental design, interior design, and marketing involving ceramic tiles.